The Genetics of Parkinson’s Disease - Levent Şimşek; Emine Berrin Yüksel; Zeliha Yücel (Genel Tıp Dergisi)
Parkinson's disease (PD) is one of the most common neurodegenerative diseases worldwide. Approximately 15% of PD patients have a family history of the disease in one or more first-degree relatives, and 5-10% of PD cases exhibit a classical Mendelian inheritance pattern. In 1997, the heritable transmission of PD was first documented. Recent studies have found 90 independent genome-wide signals at 78 loci that may be associated with PD. The identification of genes linked to PD and their functions has uncovered novel biological pathways and treatment options that play a role in the development of PD. In this article, it is aimed to review up-to-date information on the genetics of PD.